Pengaruh Gaya Kepemimpinan Terhadap Peningkatan Kinerja Pegawai Pada Dinas Pendidikan Pemuda dan Olahraga Kabupaten Mamuju - Ramadhan, Adam (LPPM Universitas Muhammadiyah Mamuju, 2022)
The method used is the Quantitative Method by distributing questionnaires. The sample used in this study the sample used was 67 employees. The sampling technique used was saturated sampling, in this study all the population was sampled with a total of 76 respondents. Data processing techniques by testing research instruments using reliability tests and simple linear regression analysis.Based on the data analysis that has been carried out in this study with the number of respondents 67 people who are State Civil Apparatus (ASN) at the Department of Education, Youth and Sports, Mamuju Regency, so that the following conclusions are drawn: 1) Based on the results of Simple linear regression using SPSS 22, it shows that the style of Leadership has an effect on Performance Improvement where the probability value is statistically 0.000 <0.05 or it can be said to be significant and the beta is 0.757. 2) Leadership style is one of the things that has the most influence on the Performance Improvement of the State Civil Apparatus (ASN) and is supported by self-awareness. This has been tested in this study and proven by the results of the simple linear regression analysis used in this study with the help of SPSS 22.